2023
DOI: 10.3390/ph16070996
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides in Pipeline: What Future for These Great Molecules?

Abstract: Cyclic peptides are molecules that are already used as drugs in therapies approved for various pharmacological activities, for example, as antibiotics, antifungals, anticancer, and immunosuppressants. Interest in these molecules has been growing due to the improved pharmacokinetic and pharmacodynamic properties of the cyclic structure over linear peptides and by the evolution of chemical synthesis, computational, and in vitro methods. To date, 53 cyclic peptides have been approved by different regulatory autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 241 publications
0
13
0
Order By: Relevance
“…Monocyclic thioacetyl-lysine peptide Compound 10 ( Table 3 ), one of the most potent Sirt2 inhibitors identified, inhibited Sirt2 with an IC 50 value of 10.1 nM with ~seven- and eight-fold selectivity for Sirt2 over Sirt1 and Sirt3, respectively [ 191 ]. Consistent with the advantages of cyclic peptide inhibitors [ 235 ], a bicyclic Sirt1-3 thioacetyl-lysine peptide inhibitor exhibited increased proteolytic stability relative to the linear peptide inhibitor [ 192 ]. The bicyclic inhibitor also demonstrated on-target cellular activity, as demonstrated by increased acetylation of the Sirt1 substrate p53 in the HCT116 colon cancer cell line and decreased proliferation of a melanoma cell line that is susceptible to Sirt1/3 inhibition [ 192 ].…”
Section: Mechanism-based Sirtuin Inhibitorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Monocyclic thioacetyl-lysine peptide Compound 10 ( Table 3 ), one of the most potent Sirt2 inhibitors identified, inhibited Sirt2 with an IC 50 value of 10.1 nM with ~seven- and eight-fold selectivity for Sirt2 over Sirt1 and Sirt3, respectively [ 191 ]. Consistent with the advantages of cyclic peptide inhibitors [ 235 ], a bicyclic Sirt1-3 thioacetyl-lysine peptide inhibitor exhibited increased proteolytic stability relative to the linear peptide inhibitor [ 192 ]. The bicyclic inhibitor also demonstrated on-target cellular activity, as demonstrated by increased acetylation of the Sirt1 substrate p53 in the HCT116 colon cancer cell line and decreased proliferation of a melanoma cell line that is susceptible to Sirt1/3 inhibition [ 192 ].…”
Section: Mechanism-based Sirtuin Inhibitorsmentioning
confidence: 91%
“…Another method to circumvent the limitations of peptide-based inhibitors [ 220 ] is cyclization to form cyclic peptides, which exhibit increased resistance to peptidases and improved cell permeability [ 235 ]. Cyclic peptides can also enhance target affinity and selectivity due to conformational restriction and maximization of favorable interactions with protein targets [ 235 ]. Therefore, cyclic peptides have increased translational potential compared to other sirtuin peptidic inhibitors.…”
Section: Mechanism-based Sirtuin Inhibitorsmentioning
confidence: 99%
“…Cyclic peptides have attracted attention as drug candidates because their properties bridge those of biologics and small molecules. As a result of their therapeutic advantages, cyclic peptides are growing rapidly as FDA-approved drug and clinical trial candidates. , Numerous cyclization strategies have been developed, including synthetic and biosynthetic methods, each of which has advantages in specific applications. For example, the biosynthetic approach enables genetic randomization to construct peptide libraries, which are compatible with selection- or phenotype-based screens directly within the producing organisms. For that reason, many genetic methods have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that 1 inhibited the cell entry of moloney murine leukemia virus (MLV) pseudoviruses (PVs) pseudotyped with the S proteins of the SARS‐CoV‐2 strains from Wuhan, the United Kingdom (B.1.1.7), and South Africa (B.1.351). Although it was recently reported that PA‐001 (PeptiAID Inc.), a macrocyclic peptide‐based compound designed to target the S‐protein of SARS‐CoV‐2, is currently under preparation for a phase 1 clinical trial, there are no commercially available drugs against COVID‐19 that target the binding to the S 2 domain of the S‐protein of SARS‐CoV‐2 [20–22] …”
Section: Introductionmentioning
confidence: 99%